GAMBARAN KECEMASAN DAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIS YANG MENJALANI HEMODIALISIS PADA MASA PANDEMI COVID-19 - Siti Febryza Indra; Bayhakki Bayhakki; Ririn Muthia Zukhra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2021)
Chronic kidney disease patients undergoing hemodialysis during the Covid-19 pandemic can experience psychological disorders such as anxiety and this also affects a person's quality of life. This study aims to describe the anxiety and quality of life of patients undergoing hemodialysis during the Covid-19 pandemic. This study used a descriptive design with the number of respondents 45 patients with purposive sampling technique. This study uses a questionnaire that has previously been tested for validity and reliability. The analysis used is univariate analysis. The majority of respondents were aged 46-55 years with a total of 16 patients (35.6%), more than half of the respondents were male with a total of 24 patients (53.3%), the highest final education was high school which is 18 patients (40 %). The majority of respondents were married were 43 patients (95.6%). Most respondents have not worked were 31 patients (68.9%). More than half of the respondents have a monthly income of IDR 0–2,500,000 which is 38 patients (84.4%). The majority of respondents had undergo hemodialysis for 12 months which is 36 patients (80%). More than half of the respondents experienced moderate anxiety were 31 patients (68.9%) and the majority of respondents had moderate quality of life were 24 patients (53.3%). Most patients with chronic kidney failure feel psychological effects such as anxiety and have an impact on the quality of life of patients while undergoing hemodialysis during the Covid-19 pandemic. Future research is recommend to increase the number of samples so that the patient's anxiety and quality of life can be better described. Keywords: anxiety, chronic kidney disease, Covid-19, hemodialysis, quality of life